Spatiotemporal Coupling Evolution Characteristics and Driving Mechanisms of Corn Cultivation and Pig Farming in China - Xuezhen Xiong; Hongping Lian; Li Fan (Land)
Corn and pig farming are representative sectors of China’s crop production and livestock industries, respectively. The spatial relationship between these two industries is of great significance for coordinating crop–livestock integration and promoting sustainable agricultural development. Therefore, this study takes corn and pig farming as focal points to examine the spatiotemporal coupling and evolutionary characteristics of these two industries and to identify the driving mechanisms underlying their spatiotemporal coupling relationship. The study results showed the following: (1) The production center for pigs is situated in southern China, whereas the corn production center is located in northern China. Temporally, the corn production center continues to shift northward, while the location of the pig production center remains relatively stable. (2) The national-level coupling development index for corn and pigs exhibits a declining trend with fluctuations and significant regional disparities. The lowest coupling development index is observed in northeastern China. (3) The “corn–pig” production balance coefficient categorizes northern regions as “more grain, fewer pigs” and southern regions as “more pigs, fewer grains”, demonstrating a persistent spatial mismatch between corn and pig production across North and South China. (4) The abundance of alternative feed grains, established industrial infrastructure, and climatic conditions are key factors driving the sustained north–south separation of these two industries. These findings provide insights into the spatiotemporal dynamics of corn and pig production in China, clarify underlying driving mechanisms, and offer valuable guidance for policy optimization aimed at enhancing crop–livestock integration and sustainable agricultural development.